2015
DOI: 10.5539/ijms.v7n3p39
|View full text |Cite
|
Sign up to set email alerts
|

Market Orientation and the Performance of Small and Medium-Sized Manufacturing Enterprises in the Accra Metropolis

Abstract: The importance of small and medium-sized manufacturing enterprises as an engine of economic growth has been widely recognized. However, despite their invaluable contribution in the Ghanaian economy, their performance has not been impressive due to the orientation of their marketing strategies. This study, therefore, sought to investigate the relationship between market orientation and the performance of small and medium-sized manufacturing enterprises in the Accra metropolis of Ghana. Given the purpose and nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…In other words, the results of the analyses suggested that the items under each variable are highly related to each other to measure their respective or the same underlying concept. This is in line with studies conducted elsewhere in Africa (e.g., Boachie-Mensah & Issau, 2015) and shows the reliability of the instrument.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, the results of the analyses suggested that the items under each variable are highly related to each other to measure their respective or the same underlying concept. This is in line with studies conducted elsewhere in Africa (e.g., Boachie-Mensah & Issau, 2015) and shows the reliability of the instrument.…”
Section: Resultssupporting
confidence: 92%
“…Customer orientation and overall market orientation had slightly higher correlation with the performance indicators used in the study. These results are in agreement with the hypotheses set and previous empirical findings indicated in the literature review (Boachie-Mensah & Issau, 2015;Boohene et al, 2012).…”
Section: Market Orientation and Performance Of Smessupporting
confidence: 93%
“…Market orientation, s one of the intangible organizational assets, especially those that are difficult for competitors to imitate these assets, create a competitive advantage that is sustainable and improves company performance (Lonial, 2015). Market orientation can e viewed from two perspectives, namely culture and behavior (Boachie-Mensah, 2015).…”
Section: Literature Review Market Orientationmentioning
confidence: 99%
“…Company performance is a multidimensional construct that does not merely include financial performance (Liao, 2011). Company performance is a measure of how well the organization or entity achieves its objectives (Boachie-Mensah, 2015). The performance is the ability to assess the level of success of a business organization both on a small and large scale.…”
Section: Company Performancementioning
confidence: 99%
See 1 more Smart Citation